Mothers' Knowledge about Exclusive Breastfeeding - Komala Sari; Tri Arianingsih; Meily Nirnasari (Indonesian Journal of Global Health Research, 2024)
Exclusive breastfeeding is one of the important pillars in supporting infant health and growth, but its coverage in Indonesia is still low, especially in rural areas such as Palmatak. Mothers' knowledge about the importance of exclusive breastfeeding influences breastfeeding practices, but various factors such as age, education, and occupation can affect their understanding. These obstacles often hinder the adoption of optimal exclusive breastfeeding practices. This study aims to describe mothers' knowledge about exclusive breastfeeding in the Palmatak Health Center area. Methods: The design of this study was descriptive quantitative. The sampling technique used simple random sampling with a sample size of 50 mothers. Data were collected using a questionnaire that measured mothers' knowledge of exclusive breastfeeding, as well as demographic characteristics such as age, education, and occupation. Data analysis was carried out using univariate analysis techniques to describe the frequency distribution and percentage of the variables studied. The results showed that the majority of respondents (76%) were in the non-risk age group, namely 20-35 years. Most mothers had a high school education/equivalent (36%), and most worked as self-employed (30%). Regarding maternal knowledge about exclusive breastfeeding, 52.94% had low knowledge, while 47.06% had high knowledge. Factors such as limited access to health information and the influence of local cultural habits are the main obstacles in increasing maternal knowledge about exclusive breastfeeding. This study concluded that despite high knowledge among some mothers, many mothers still do not understand the importance of exclusive breastfeeding. Health centers and health cadres have an important role in increasing maternal knowledge through community-based education programs that are tailored to local conditions. Interventions based on social and cultural contexts can be more effective in increasing exclusive breastfeeding coverage in rural areas.